Environmental policies and practices in Cruise Ports: Waste reception facilities in the Med - Athanasios A. Pallis; Aimilia A. Papachristou; Charalampos Platias (SPOUDAI - Journal of Economics and Business, 2017)
With cruise activities continuing to grow, the cruise world and related decision makers take initiatives aiming to handle the produced externalities. Among the key environmental issues is the handling of the various wastes produced on cruise ships. In recent times, cruise lines and ports have put efforts into reducing, selecting and managing generated wastes implementing the requirements of the international regulatory framework (MARPOL 73/78), as well as those imposed by the European legislation. This study focuses on the state port reception facilities (PRF) in the case of the second biggest cruise region of the world, the Mediterranean and its adjoining seas. In particular, it sheds light on the extent that the current practices of cruise ports have achieved a satisfactory level of compliance to the emerging environmental related international regulatory framework. The paper does so via a survey that maps the existing conditions and port based practices followed by 40 port entities that manage 52 cruise ports in the region. The findings record the available facilities, technologies and services suggesting a widespread effective correspondence to required adjustment. It also details a variation as regards the charging practices, that might affect the level playing field. The analysis generates knowledge on the emphasis given by cruise ports in addressing environment challenges. Given that the European Directive governing PRF is currently (2016) under review, the study provides practical recommendations to decision makers and practitioners on what can be done so as to further secure a sustainable cruise future.
Keywords: F64; L91; Q53; 330; cruise ports; waste reception facilities; Mediterranean; ports; MARPOL; sustainable cruise